Composite material containing metal monatomic and intermetallic compound, preparation and application

By preparing nitrogen- and sulfur-co-doped porous carbon-supported composite materials of metal single atoms and intermetallic compound particles, the problems of high cost and insufficient catalytic selectivity of fuel cell catalysts were solved, achieving high-efficiency oxygen reduction catalytic activity and high utilization of precious metals.

CN121035236APending Publication Date: 2025-11-28BEIJING SINGLE ATOM SITE CATALYSIS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410667192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing fuel cell catalysts use a high amount of precious metals in the membrane electrode assembly, resulting in high costs. Single-atom catalysts have insufficient catalytic selectivity and stability at the cathode oxygen reduction reaction end, and the size of nanoparticles tends to increase during the phase transition from disordered alloys to ordered intermetallic compounds.

Method used

A composite material with an average particle size ≤4nm was prepared by using nitrogen and sulfur co-doped porous carbon-supported metal single atoms and intermetallic compound particles. Ultra-small intermetallic compounds were formed through pyrolysis and acid etching, combined with heat treatment under a reducing atmosphere.

Benefits of technology

It improves oxygen reduction catalytic activity and the utilization rate of precious metal atoms, achieving high-efficiency and low-cost catalyst performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035236A_ABST
    Figure CN121035236A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material containing metal single atoms and intermetallic compounds, which comprises Ma metal single atoms and intermetallic compound particles loaded on a carrier, and the carrier is nitrogen and sulfur co-doped porous carbon; the Ma metal is a 3d transition metal, the intermetallic compound is formed by a Pt metal and an Mb metal, and the Mb is the 3d transition metal. The monatomic sites in the composite material are uniformly dispersed, the particle size of the intermetallic compound is smaller than or equal to 4 nm, the atom utilization rate is high, a synergistic effect is formed between the intermetallic compound particles and the monatomic sites, and the composite material has a good application prospect in the field of fuel cell related cathode oxygen reduction catalytic reactions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of fuel cell catalysts, and particularly relates to single-atom and intermetallic compound composite materials, a preparation method and application thereof. BACKGROUND

[0002] As an important part of the "green hydrogen" end application, fuel cell technology has a profound significance in alleviating energy crisis and environmental problems due to its high energy conversion efficiency and net zero emission. However, the high membrane electrode noble metal consumption makes the fuel cell catalyst cost high, which limits the commercial development of fuel cell vehicles. Therefore, the development of high-efficiency and low-cost catalysts is the key to solving the cost problem. Single-atom catalysts have unique advantages in reducing costs due to their nearly 100% atom utilization rate, but their catalytic selectivity and stability on the cathode oxygen reduction reaction side still need to be improved. The strong coupling between single atoms and nanoscale provides an opportunity to solve this problem, and the ordered atomic arrangement of intermetallic compounds can maximize the gain effect of disordered alloys. However, high-temperature heat treatment is usually required for the phase transition from disordered alloys to ordered intermetallic compounds, which inevitably causes the rapid increase of nanoparticle size due to the high-temperature induced directional migration of atoms. Therefore, it is a great challenge to develop a simple and easy-to-operate synthesis method to anchor single atoms and ultra-small intermetallic compounds to resist metal sintering. SUMMARY

[0003] The present application discloses a composite material containing metal single atoms and intermetallic compound particles, which comprises M a metal single atoms and intermetallic compound particles, and a carrier, wherein the carrier is a nitrogen and sulfur co-doped porous carbon; the M a metal is a 3d transition metal, and the intermetallic compound is an intermetallic compound formed by Pt metal and M b metal, and M b is a 3d transition metal. In the composite material, the average particle size of the intermetallic compound is <= 4 nm. The composite material can improve the oxygen reduction catalytic activity and noble metal atom utilization rate.

[0004] wherein the 3d transition metal is a third period transition metal. Preferably, M a is one of Mn, Fe, Co, Ni, Cu or Zn; M b is selected from one or more of Mn, Fe, Co, Ni, Cu or Zn. In the present application, M a is implemented as Fe, M b is implemented as Mn, Fe, Co, Ni, Cu or Zn.

[0005] The mass fraction of Pt in the composite material is 5% to 40%, based on the total weight of the composite material.

[0006] The application also provides a preparation method of the composite material containing metal single atoms and intermetallic compound particles, and the specific steps are as follows:

[0007] S1, mixing M a The metal salt, the nitrogen-containing small molecule monomer, the sulfur-containing small molecule monomer and the crosslinking agent are reacted in a solvent to form a polymer containing M a metal;

[0008] S2, pyrolyzing the polymer obtained in S1, and performing acid etching on the obtained pyrolysis product to form a nitrogen and sulfur co-doped porous carbon loaded M a single atom material;

[0009] S3, mixing the single atom material obtained in S2, M b metal salt, Pt metal salt and a solvent, and obtaining a solid powder after evaporating the solvent, and then performing heat treatment on the solid powder in a reducing atmosphere to obtain the composite material containing metal single atoms and intermetallic compound particles.

[0010] In the step S1, the M a metal salt is one of a manganese salt, an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt; and the M b metal salt is one of a manganese salt, an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt; the solvent is one or a mixture of more than one of water, ethanol, methanol or isopropanol; the pyrolysis temperature is 800-900℃, the pyrolysis time is 1-3h, and the heating rate is 1-10℃ / min.

[0011] The nitrogen-containing small molecule monomer is one or a mixture of more than one of a pyrrole, C 1-6 alkyl-substituted pyrrole, aniline, C 1-6 alkyl-substituted aniline; and the sulfur-containing small molecule monomer is thiophene or C 1-6 alkyl-substituted thiophene; and the crosslinking agent is dimethoxymethane.

[0012] In fact, whether the nitrogen-containing small molecule monomer and the sulfur-containing small molecule monomer are substituted or not has little effect on the preparation of the material. After the final pyrolysis and acid treatment processes, a carbon-based carrier containing only nitrogen, sulfur and carbon as main elements is formed.

[0013] More specifically, the preparation method of the super-crosslinked polymer is as follows:

[0014] Anhydrous ferric chloride, dimethoxymethane, nitrogen-containing small molecules and sulfur-containing small molecules are uniformly mixed in 1,2-dichloroethane solvent for crosslinking for 24h, and the obtained product is washed with methanol and dried to obtain the super-crosslinked polymer;

[0015] The molar ratio of the anhydrous ferric chloride, dimethoxymethane, nitrogen-containing small molecule monomer and sulfur-containing small molecule monomer is 4:4:1:1; the crosslinking temperature is 60℃;

[0016] Preferably, the nitrogen-containing small molecule monomer is preferably pyrrole, aniline; the sulfur-containing small molecule monomer is preferably thiophene.

[0017] In the S2 step, the acid is one or more of sulfuric acid, hydrochloric acid, nitric acid or perchloric acid.

[0018] In the S3 step, the platinum salt is M b The atomic ratio of the metal salt is 1:(0.3-3), and the solvent is one or more of water, ethanol, methanol, isopropanol;

[0019] The reducing atmosphere is hydrogen or a mixture of hydrogen and an inert gas such as nitrogen. Preferably, it is a mixture of hydrogen and nitrogen, wherein the volume fraction of hydrogen is 5%-10% and the volume fraction of nitrogen is 90%-95%. The heat treatment temperature is 800-950℃, the heat treatment time is 2-4h, and the heating rate is 1-10℃ / min.

[0020] Preferably, the sum of the mass fraction of noble metal Pt in the obtained metal monatomic and intermetallic compound composite material is 5%-40%;

[0021] Preferably, the platinum salt is one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, potassium chloroplatous acid, platinum acetylacetate, dichloroplatinum, and tetrachloroplatinum.

[0022] Preferably, the manganese salt is one of manganese chloride, manganese acetate hydrate, manganese acetylacetate, manganese carbonate, manganese sulfate, and manganese nitrate hydrate, the iron salt is one of ferric chloride, ferrous chloride, iron acetylacetate, iron acetate, iron sulfate, and iron nitrate, the cobalt salt is one of anhydrous cobalt sulfate, cobalt acetate, anhydrous cobalt chloride, cobalt nitrate, and cobalt acetylacetate, the nickel salt is one of nickel chloride, nickel acetylacetate, and nickel nitrate, the copper salt is one of cuprous chloride, anhydrous copper sulfate, copper chloride dihydrate, and anhydrous copper chloride, and the zinc salt is one of zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, and zinc acetylacetate hydrate.

[0023] The application also provides an application of the aforementioned metal monatomic and intermetallic compound particle composite material, which is used as a catalyst, preferably for a fuel cell cathode oxygen reduction catalytic reaction.

[0024] Compared with the prior art, the strong coupling synergy effect between the metal monatomic sites and the ultra-small intermetallic compounds in the composite material can improve the oxygen reduction reaction activity and selectivity while ensuring high atomic utilization. Attached Figure Description

[0025] Figure 1 The diagram shows the material analysis of Example 1, where (a) is the X-ray diffraction pattern of the nitrogen and sulfur co-doped carbon-supported Fe single atoms and PtFe intermetallic compound prepared in Example 1 of the present invention, with reference to the Pt / C and PtFe / C samples prepared using Vulcan XC-72 as carbon support. Figure 1 (b) is a low-magnification electron microscope image of the above composite material, with the inset image showing the particle size distribution curve. Figure 1 Image (c) is an electron microscope image of the above composite material at atomic-scale resolution.

[0026] Figure 2 The images show X-ray diffraction patterns (a), low-magnification electron microscope images (b), and particle size distribution curves (c) of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and PtCo intermetallic compounds prepared in Example 2 of this invention.

[0027] Figure 3 The images show X-ray diffraction patterns (a), low-magnification electron microscope images (b), and particle size distribution curves (c) of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and PtNi intermetallic compounds prepared in Example 3 of this invention.

[0028] Figure 4 The images show X-ray diffraction patterns (a), low-magnification electron microscope images (b), and particle size distribution curves (c) of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and Pt3Mn intermetallic compounds prepared in Example 4 of this invention.

[0029] Figure 5 X-ray diffraction pattern (a), low-magnification electron microscope image (b), and particle size distribution curve (c) of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and Pt3Zn intermetallic compound prepared in Example 5 of this invention.

[0030] Figure 6 The graph shows the oxygen reduction polarization curves of the composite materials prepared in Examples 1-5 of this invention as catalysts and commercial Pt / C catalysts.

[0031] Figure 7 The bar chart shows the comparison of the oxygen reduction performance of the composite material prepared in Example 1 of this invention as a catalyst with that of a commercial Pt / C catalyst. Detailed Implementation

[0032] To facilitate understanding of the present invention, the following detailed description, in conjunction with specific embodiments and accompanying drawings, will illustrate the invention in detail. However, it should be understood that this description is merely illustrative of the features and advantages of the invention and is not intended to limit the scope of the claims. Furthermore, the technical features described in the various specific embodiments of the invention below can be combined with each other as long as they do not conflict with each other.

[0033] Example 1

[0034] (1) Anhydrous ferric chloride, dimethoxymethane, pyrrole, and thiophene were uniformly mixed in a molar ratio of 4:4:1:1 in a three-necked flask containing 100 mL of 1,2-dichloroethane solvent. The mixture was refluxed at 60 °C for 24 h to achieve full crosslinking. The resulting product was washed with methanol and dried to obtain the hypercrosslinked polymer. Then, 100 mg of the dried powder was added to 10 mL of a 1 mg / mL anhydrous ferric chloride / isopropanol mixed solution and ultrasonically mixed. The solvent was evaporated at 65 °C and the mixture was thoroughly dried before being transferred to a tube furnace. The mixture was pyrolyzed at 800 °C for 2 h under a nitrogen atmosphere at a heating rate of 5 °C / min. After the sample cooled to room temperature, the resulting solid powder was placed in a 0.5 mol / L sulfuric acid solution for acid treatment in an oil bath at 90 °C. The mixture was then filtered, washed until neutral, and dried to obtain nitrogen- and sulfur-doped porous carbon-supported Fe single-atom material.

[0035] (2) The obtained Fe single-atom material was used as a carrier for secondary loading and anchoring of PtFe ultra-small intermetallic compounds. Specifically, chloroplatinic acid and anhydrous ferric chloride were dissolved in water at an atomic ratio of 1:1. The Fe single-atom material was then dispersed in the mixed solution. After thorough impregnation by alternating sonication and stirring, the solvent was evaporated by heat treatment. After the obtained solid powder was thoroughly dried, it was ground evenly in an agate mortar and then transferred to a tube furnace. It was reduced at 300°C for 2 hours in a hydrogen / nitrogen mixture with a hydrogen integral of 5%, and then heat-treated at 900°C for 2 hours at a heating rate of 10°C / min. After the sample cooled to room temperature, a composite material of nitrogen and sulfur co-doped porous carbon anchored Fe single atoms and PtFe intermetallic compounds was obtained.

[0036] Figure 1 (a) is the XRD pattern of the Fe single-atom and PtFe intermetallic compound composite material provided in Specific Embodiment 1 of the present invention. It can be seen that it matches the standard PDF card of PtFe intermetallic compounds, and the number of diffraction peaks is significantly different from that of the Vulcan XC-72 loaded Pt sample. Moreover, the half-peak width of the diffraction peaks is wider than that of the Vulcan XC-72 loaded PtFe sample, indicating that its grain size is smaller.

[0037] Figure 1(b) is a low-magnification electron microscope image of the above material, and the embedded particle size distribution curve shows that its average particle size is less than 4 nm.

[0038] Figure 1 (c) is an electron microscope image of the above material at atomic scale resolution. Isolated bright spots represent Fe single-atom sites in the material, and the alternating rows of bright and dark atoms in the nanoparticles represent the ordered atomic arrangement of the PtFe particles, fully confirming the formation of intermetallic compounds.

[0039] Example 2

[0040] (1) The steps are the same as in Specific Implementation Example 1;

[0041] (2) The obtained Fe single-atom material was used as a carrier for secondary loading and anchoring of PtCo ultrasmall intermetallic compounds. Specifically, chloroplatinic acid and cobalt chloride were dissolved in water at an atomic ratio of 1:1. Then, the Fe single-atom material was dispersed in the mixed solution. After thorough impregnation by alternating sonication and stirring, the solvent was evaporated by heat treatment. After thorough drying, it was ground evenly in an agate mortar and then transferred to a tube furnace. It was reduced at 300°C for 2 hours in a hydrogen / nitrogen mixture with a hydrogen integral of 5%. Then, it was heat-treated at 950°C for 2 hours at a heating rate of 10°C / min. After the sample cooled to room temperature, the nitrogen and sulfur co-doped porous carbon anchored Fe single-atom and PtCo intermetallic compound composite material was obtained.

[0042] Figure 2 The images show X-ray diffraction patterns, low-magnification electron microscope images, and particle size distribution curves of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and PtCo intermetallic compounds prepared in Example 2 of this invention.

[0043] The XRD pattern shows that it matches the standard PDF card for PtCo intermetallic compounds. Low-magnification electron microscopy images indicate uniform particle distribution with no obvious agglomeration. The particle size distribution curve shows that the average PtCo particle size is less than 4 nm.

[0044] Example 3

[0045] (1) The steps are the same as in Specific Implementation Example 1;

[0046] (2) The obtained Fe single-atom material was used as a carrier for secondary loading and anchoring of PtNi ultra-small intermetallic compounds. Specifically, chloroplatinic acid and nickel chloride were dissolved in water at an atomic ratio of 2:3. Then, the Fe single-atom material was dispersed in the mixed solution. After thorough impregnation by alternating sonication and stirring, the solvent was evaporated by heat treatment. After thorough drying, it was ground evenly in an agate mortar and then transferred to a tube furnace. It was reduced at 300°C for 2 hours in a hydrogen / nitrogen mixture with a hydrogen gas integral of 5%. Then, it was heat-treated at 950°C for 2 hours at a heating rate of 10°C / min. After the sample cooled to room temperature, the composite material of Fe single-atom and PtNi intermetallic compounds anchored by nitrogen and sulfur co-doped porous carbon was obtained.

[0047] Figure 3 The images show X-ray diffraction patterns, low-magnification electron microscope images, and particle size distribution curves of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and PtNi intermetallic compounds prepared in Example 3 of this invention.

[0048] The XRD pattern shows that it matches the standard PDF card for PtNi intermetallic compounds. Low-magnification electron microscopy images indicate uniform particle distribution with no obvious agglomeration. The particle size distribution curve shows that the average PtNi particle size is less than 4 nm.

[0049] Example 4

[0050] (1) The steps are the same as in Specific Implementation Example 1;

[0051] (2) The obtained Fe single-atom material was used as a carrier for secondary loading and anchoring of Pt3Mn ultrasmall intermetallic compounds. Specifically, chloroplatinic acid and manganese chloride were dissolved in water at an atomic ratio of 3:1. Then, the Fe single-atom material was dispersed in the mixed solution. After thorough impregnation by alternating sonication and stirring, the solvent was evaporated by heat treatment. After thorough drying, it was ground evenly in an agate mortar and then transferred to a tube furnace. It was reduced at 300℃ for 2 hours in a hydrogen / nitrogen mixture with a hydrogen integral of 5%. Then, it was heat-treated at 950℃ for 2 hours at a heating rate of 10℃ / min. After the sample cooled to room temperature, the composite material of nitrogen and sulfur co-doped porous carbon anchored Fe single atoms and Pt3Mn intermetallic compounds was obtained.

[0052] Figure 4 The images show X-ray diffraction patterns, low-magnification electron microscope images, and particle size distribution curves of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and Pt3Mn intermetallic compounds prepared in Example 4 of this invention.

[0053] The XRD pattern shows that it matches the standard PDF card for Pt3Mn intermetallic compounds. Low-magnification electron microscopy images indicate uniform particle distribution with no obvious agglomeration. The particle size distribution curve shows that the average particle size of Pt3Mn is less than 4 nm.

[0054] Example 5

[0055] (1) The steps are the same as in Specific Implementation Example 1;

[0056] (2) The obtained Fe single-atom material was used as a carrier for secondary loading and anchoring of Pt3Zn ultrasmall intermetallic compounds. Specifically, chloroplatinic acid and zinc chloride were dissolved in water at an atomic ratio of 3:2. Then, the Fe single-atom material was dispersed in the mixed solution. After thorough impregnation by alternating sonication and stirring, the solvent was evaporated by heat treatment. After thorough drying, it was ground evenly in an agate mortar and then transferred to a tube furnace. It was reduced at 300°C for 2 hours in a hydrogen / nitrogen mixture with a hydrogen integral of 5%. Then, it was heat-treated at 800°C for 2 hours at a heating rate of 10°C / min. After the sample cooled to room temperature, the composite material of nitrogen and sulfur co-doped porous carbon anchored Fe single atoms and Pt3Zn intermetallic compounds was obtained.

[0057] Figure 5 The images show X-ray diffraction patterns, low-magnification electron microscope images, and particle size distribution curves of the nitrogen- and sulfur-co-doped carbon-supported Fe single atoms and Pt3Zn intermetallic compounds prepared in Specific Embodiment 5 of the present invention.

[0058] The XRD pattern shows that it matches the standard PDF card for Pt3Zn intermetallic compounds. Low-magnification electron microscopy images indicate uniform particle distribution with no obvious agglomeration. The particle size distribution curve shows that the average particle size of Pt3Zn is less than 4 nm.

[0059] Application Test Example 6

[0060] The catalyst powder was ultrasonically mixed with a 1‰ Nafion / isopropanol solution. 10 μL of the dispersion was then pipetted onto a pre-polished glassy carbon electrode surface. After evaporating the solvent under an infrared lamp, a uniform catalyst layer was formed. Subsequently, using this as the working electrode, reversible hydrogen as the reference electrode, and a carbon rod as the counter electrode, the catalyst was subjected to an infrared lamp at 50 mV s⁻¹. -1 and 5mV s -1 Cyclic voltammetry and linear sweep voltammetry were performed using sweep rate tests. The catalytic activity for oxygen reduction was evaluated by calculating the half-wave potential and the mass-to-volume activity at 0.9 V.

[0061] Figure 6The figures show the oxygen reduction polarization curves of the nitrogen- and sulfur-co-doped carbon-supported Fe single-atom and Pt-based intermetallic compound composite materials in Examples 1-5, compared to those of commercial Pt / C. The results indicate that the oxygen reduction catalytic activity of the composite materials is significantly superior to that of the Vulcan XC-72-supported Pt / C and PtFe / C materials. Furthermore, Figure 7 The mass-to-activity ratio of the nitrogen- and sulfur-co-doped carbon-supported Fe single-atom and PtFe intermetallic compound composite material with the best performance among the above composite materials was calculated, which is ~12.5 times that of commercial Pt / C at a potential of 0.9V.

[0062] The above-described specific embodiments are intended to facilitate implementation and utilization of the present invention by those skilled in the art. However, this does not mean that the present invention is limited to the above specific embodiments. Any modifications, equivalent substitutions, and improvements made within the principles and spirit of the present invention should be included within the protection scope of the present invention.

Claims

1. A composite material containing metal single atoms and intermetallic compound particles, comprising M supported on a carrier. a Metal single-atom and intermetallic compound particles, wherein the support is nitrogen- and sulfur-doped porous carbon, wherein M a It is a 3d transition metal, and its intermetallic compound is Pt metal with M. b Intermetallic compounds formed by metals, M b As a 3d transition metal, in intermetallic compounds, platinum and M b The atomic ratio is 1:(0.3~3).

2. The material as claimed in claim 1, wherein, M a Selected from one of Mn, Fe, Co, Ni, Cu or Zn, preferably Fe; M b It can be Mn, Fe, Co, Ni, Cu, or Zn.

3. The material as described in claim 1 or 2, wherein, The average particle size of the intermetallic compound is less than or equal to 4 nm, and the mass fraction of Pt in the composite material is 5% to 40% based on the total weight of the composite material.

4. A method for preparing the composite material according to any one of claims 1-3, comprising the following steps: S1, M a Metal salts, nitrogen-containing small monomers, sulfur-containing small monomers, and crosslinking agents react in a solvent to form M... a Hypercrosslinked polymers of metals; S2, the polymer obtained from the pyrolysis of S1, and the acid etching of the resulting pyrolysis product to form nitrogen- and sulfur-co-doped porous carbon-supported M. a Single-atom materials; S3, the single-atom material obtained in S2, M b Metal salts and Pt metal salts are mixed with solvents, and the solvents are evaporated to obtain solid powders. The solid powders are then heat-treated in a reducing atmosphere to obtain composite materials containing metal single atoms and intermetallic compound particles. in, The nitrogen-containing small molecule monomer is pyrrole, C 1-6 Alkyl-substituted pyrroles, aniline, C 1-6 One or more of alkyl-substituted anilines; the sulfur-containing small molecule monomer is thiophene or C 1-6 The alkyl-substituted thiophene is used; the crosslinking agent is dimethoxymethane; the reducing atmosphere is hydrogen or a mixture of hydrogen and an inert gas; the acid is one or more of sulfuric acid, hydrochloric acid, nitric acid, or perchloric acid; and the solvent is one or more of water, ethanol, methanol, or isopropanol.

5. The method of claim 4, wherein, In step S1, the M a The metal salt is one of the following: manganese salt, iron salt, cobalt salt, nickel salt, copper salt, or zinc salt; M b The metal salt is one of manganese salt, iron salt, cobalt salt, nickel salt, copper salt, or zinc salt; in step S2, the pyrolysis temperature is 800-900℃ and the pyrolysis time is 1-3h.

6. The method of claim 4 or 5, wherein in step S3, the platinum salt and M b The atomic ratio of the metal salt is 1:(0.3~3); the reducing atmosphere is a mixture of hydrogen and nitrogen, wherein, The volume fraction of hydrogen is 5% to 10%, and the volume fraction of nitrogen is 90% to 95%.

7. The method according to any one of claims 4-6, wherein, The preparation method of the hypercrosslinked polymer is as follows: anhydrous ferric chloride, dimethoxymethane, nitrogen-containing small molecules, and sulfur-containing small molecules are uniformly mixed in 1,2-dichloroethane solvent for crosslinking. The resulting product is washed with methanol and dried to obtain the hypercrosslinked polymer.

8. The method of claim 7, wherein, The molar ratio of anhydrous ferric chloride, dimethoxymethane, nitrogen-containing small molecule monomer, and sulfur-containing small molecule monomer is 4:4:1:1; the crosslinking temperature is 60℃.

9. The method according to any one of claims 4-8, wherein, The platinum salt is one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, potassium chloroplatinate, platinum acetylacetonate, platinum dichloride, and platinum tetrachloride; the manganese salt is one of manganese chloride, manganese acetate hydrate, manganese acetylacetonate, manganese carbonate, manganese sulfate, and manganese nitrate hydrate; the iron salt is one of ferric chloride, ferrous chloride, ferric acetylacetonate, ferric acetate, ferric sulfate, and ferric nitrate; the cobalt salt is one of anhydrous cobalt sulfate, cobalt acetate, anhydrous cobalt chloride, cobalt nitrate, and cobalt acetylacetonate; the nickel salt is one of nickel chloride, nickel acetylacetonate, and nickel nitrate; the copper salt is one of cuprous chloride, anhydrous copper sulfate, copper chloride dihydrate, and anhydrous copper chloride; and the zinc salt is one of zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, and zinc acetylacetonate hydrate.

10. The application of a composite material containing metal single atoms and intermetallic compound particles, the material being used as a catalyst in the oxygen reduction catalytic reaction at the cathode of a fuel cell, said composite material being prepared as described in any one of claims 1-3, or by the method described in any one of claims 4-9.